The effect of industry restructuring on peer firms - Alex Holcomb; Paul Mason (Journal of Risk and Financial Management, 2021)
We study the bond price reaction of a merged firms peers, in order to better understand how the market responds to a restructuring. We argue that a merger announcement may signal the possibility of a merger wave to the industry, and in doing so, increase the conditional probability that peer firms might themselves be acquired in the future. However, while peer firm equity holders expect a direct benefit from a potential acquisition - in the form of a price premium-peer firm bond holders can only expect an indirect benefit - in the form of a risk reduction. Consistent with these hypotheses, we show that price reactions are stronger for firms that have a higher unconditional probability of being acquired ex-ante. In addition, we document that, cross-sectionally, the abnormal returns we observe from peer bondholders are concentrated among firms that have the highest expected risk reduction benefit from a potential acquisition. In order to distinguish a potential reduction in risk as the explicit return driver, we show that abnormal bond returns within firm (between different bond issues) are also concentrated among issues that have the highest expected risk reduction benefit.
Keywords: G12; G14; G32; G34; 330; acquisitions; bond prices; competition; equity prices; mergers